1995
DOI: 10.1097/00000542-199507000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Halothane on Glutamate Receptor-mediated Excitatory Postsynaptic Currents

Abstract: Halothane depresses glutamatergic EPSCs irrespective of receptor subtype, most likely by inhibition of glutamate release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(47 citation statements)
references
References 52 publications
3
44
0
Order By: Relevance
“…It is widely held that general anesthetics influence glutamate neurotransmission via presynaptic sites of action (Maclver et al 1996;Perouansky et al 1995;Schlame and Hemmings 1995;Wu et al 2004). However, the literature is unclear regarding the ability of anesthetics to influence the neurotransmitter release machinery itself.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely held that general anesthetics influence glutamate neurotransmission via presynaptic sites of action (Maclver et al 1996;Perouansky et al 1995;Schlame and Hemmings 1995;Wu et al 2004). However, the literature is unclear regarding the ability of anesthetics to influence the neurotransmitter release machinery itself.…”
Section: Discussionmentioning
confidence: 99%
“…(Zorychta and Capek 1978;Takenoshita and Takahashi 1987;Kullmann et al 1989;Miao et al 1995; In Caenorhabditis elegans, two sorts of approaches have been taken. Using supraclinical concentrations of VAs Perouansky et al 1995;Schlame and Hemmings 1995;MacIver et al 1996;Nishikawa and MacIver 2000) to produce immobilization as an anesthetic endpoint, and postsynaptic anesthetic effects ( Jones et al 1992; Morgan, Sedensky, and co-workers have isolated novel Mihic et al 1997;Patel et al 1999;Yamakura et al 2001) mutants that are VA hypersensitive or that are suppreshave been observed that might contribute to a state of sors of the VA-hypersensitive phenotype (Morgan and general anesthesia. However, establishing a causal link Cascorbi 1985; Sedensky and Meneely 1987; Morgan between VA effects in vitro and in vivo has been problemet al 1988;Morgan et al 1990; Morgan and Sedensky atic.…”
Section: Espite Longstanding Efforts Volatile Anestheticmentioning
confidence: 99%
“…sensitivity to supraclinical VA concentrations in the immobilization assay (Humphrey et al 2002) et al 1989;Miao et al 1995; and from our own mutagenesis screens as described below. Perouansky et al 1995;Schlame and Hemmings 1995; All strains were grown on nematode growth media (NGM) MacIver et al 1996;Nishikawa and Kidokoro 1999; agar seeded with OP50 bacteria (Brenner 1974 transmitter release, an action that could be responsible for at least some behavioral effects of anesthetics. In tg26,n686),.…”
Section: Espite Longstanding Efforts Volatile Anestheticmentioning
confidence: 99%
“…Prolongation of synaptic inhibition by positive modulation of postsynaptic GABA A receptor function at GABAergic synapses is an important component of the depressant effects of volatile anesthetics and the primary action of several chemically distinct intravenous anesthetics at clinical concentrations (Hales and Lambert, 1991;Franks and Lieb, 1994;MacIver, 1997;Wakasugi et al, 1999;Buggy et al, 2000). Depression of excitatory transmission is also observed at clinical concentrations of many general anesthetics, particularly volatile anesthetics (Perouansky et al, 1995;MacIver et al, 1996;Ouanounou et al, 1998;Wakasugi et al, 1999). The mechanisms of these effects are unclear.…”
Section: Greater Inhibition Of L-[mentioning
confidence: 99%